PENGARUH CURRENT RASIO DAN DEBT TO EQUITY RATIO TERHADAP HARGA SAHAM DI PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013 – 2017 - Dwi Fitrianingsih; Yogi Budiansyah (Jurnal Riset Akuntansi Terpadu, 2019)
This study aims to determine the effect of Current Ratio (CR) on Stock Prices, the effect of Debt to Equity Ratio (DER) on Stock Prices and to know the effect of Current Ratio ( CR) and simultaneous Debt to Equity Ratio (DER) to Stock Prices in Food and Beverage Companies for the 2013-2017 period. This study uses a descriptive type of statistical analysis with a quantitative approach. The population of this research are 16 companies. This study used financial report data with time series for the last 5 years. Sample selection through purposive sampling method There are 13 food and beverages companies that meet the criteria as a sample of research so that the research data amounted to 65.The results of this research are Current Ratio has a significant effect on the Stock Price variable, the results of this research indicate that the increasing Current Ratio will increase the Stock Price. Debt to Equity Ratio has a significant effect on the Stock Price variable, the results of this research indicate that the low Debt to Equity Ratio will increase the Stock Price. independent variable Current Ratio and Debt to Equity Ratio simultaneously have a significant effect on the Stock Price variable.